D8.5 Report on ECoE Networking & Knowledge Hub - Anayiotos, Andreas; Themistocleous, Kyriacos; Kaskara, Mariza; Karamanolis, George; Psallidas, Michael; Routsis, Fotios; Kinanlis, Panagiotis; Athanasiou, Steriani; Philimis, Panayiotis (My University, 2022)
This document, entitled “D8.5 Report on ECoE Networking & Knowledge Hub”, provides a short description of the platforms content. The design and development of the platforms is scheduled to be implemented after Month 18. This deliverable presents the main motivation and ideas behind the functionality of the platforms. A full description of the platforms’ content in its final form will be available in D8.6 – Report on ECoE Networking & Knowledge Hub (update 1). The main scope of the platforms is to foster the cross-fertilisation of ideas and uptake of ECoE’s research and innovation output and facilitate ECoE cross-departmental and external access to state-of-the-art IP.
Keywords: Remote Sensing; EXCELSIOR; ERATOSTHENES Centre of Excellence; Earth Observation; Digital Innovation Hub; EMMENA